The Effect of International Tourist Arrivals on Regional Development in East Nusa Tenggara (NTT) Province - Saputra, Angga; Riyanto, Riyanto (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
The government of Indonesia has established Komodo National Park as one of the priority tourist destinations since 2015 to stimulate the number of international tourist arrivals to Komodo National Park, located in West Manggarai Regency, East Nusa Tenggara Province (NTT). This study aims to analyze the spillover effect of the surge of international tourists in Komodo National Park and its impact on the regional economy in NTT. This study used the Spatial Autoregressive (SAR) and Spatial Durbin Model (SDM) methods on district-level data from 2012 to 2018 and found that the surge of international tourists visiting Komodo National Park had a positive and significant spillover effect on the increase of tourism activities in other tourist destinations in NTT. The rise of tourism activity impacted regional economic growth significantly in West Manggarai Regency and other districts in NTT, and the tourism growth positively influenced the regional economic convergence in NTT.